Clinical usefulness of anti-α3Gal immunoglobulin E assays for cetuximab-mediated anaphylaxis in head and neck cancer - Y. Pointreau; C. Freneaux; T. Bejan-Angoulvant; D. Ternant; G. Calais; H. Watier (Immuno-Oncology and Technology)
Background: Fatal anaphylactic reactions to cetuximab remain a clinical issue, although they are associated with preexisting immunoglobulin E (IgE) directed against the galactose-α1,3-galactose epitope (α3Gal). We aimed to compare the clinical usefulness of the two assays and determine the prevalence of preexisting anti-α3Gal IgE. Patients and methods: An anti-α3Gal IgE assay was developed (70BP assay) and compared with a commercial assay [bovine thyroglobulin (bTG) assay]. Both assays were applied to two cohorts: 299 healthy blood donors and 41 patients with head and neck cancer treated with cetuximab, including four patients with a history of anaphylactic reaction (9.8%). Results: The prevalence of anti-α3Gal IgE was 6% and 5% using 70BP and bTG assays, respectively, in healthy blood donors. Among the head and neck cancer patients, the four who had an anaphylactic reaction were included in the seven (17.1%) and six (14.6%) patients with a signal above the detection threshold using the 70BP and bTG assays, respectively. This resulted in a sensitivity and negative predictive value of 100% for both assays, with a specificity of 91.9% and 94.6%, respectively, and a positive predictive value of 57.1% and 66.6% for the 70BP and bTG assays, respectively. Using an optimized threshold in the bTG assay, the prevalence of anti-α3Gal IgE in blood donors decreased to 1.3%, and five patients (12.2%) were eventually considered positive, giving a specificity of 97.3% and a positive predictive value of 80%. Conclusion: The predictive value of anti-α3Gal IgE using these two assays was excellent and useful in clinical practice.